Analisis Hasil Pemeriksaan Kreatinin pada Sampel dengan Penambahan Hemolisat Berbagai Level - Putri, Salsa Amelia (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Examination of creatinine levels in the blood is one of the parameters used to assess kidney function because the concentration in plasma and its excretion in the urine in 24 hours is relatively constant. Hemolyzed plasma samples can affect creatinine levels with the examination results tending to decrease when compared to normal plasma examination results. Objective: To assess the percentage decrease or increase in mean, precision, accuracy, and clinical differences in creatinine assay by Jaffe Reaction Method using plasma samples with various levels of hemolysate added against samples without hemolysate added. Methods: Pure experiment (true experimental) with research samples in the form of venous blood of students and female students of the D-3 Medical Laboratory Technology Study Program of the East Kalimantan Ministry of Health Polytechnic as many as 40 samples. This research was conducted at the Hematology Laboratory and Clinical Chemistry Laboratory of the Poltekkes Kemenkes Kalimantan Timur. Data were obtained through measurement of the object of research after being treated in the form of the addition of various levels of hemolysate. Data analysis using Microsoft Excel application. Results: The mean decrease in creatinine test results of insignificant hemolysis and mild hemolysis samples against nonhemolyzed plasma samples was 6% and 8%. Accuracy value <5% in creatinine examination of insignificant hemolysis and mild hemolysis samples by -5% and -6%. The precision value >6% in the creatinine examination of insignificant hemolysis and mild hemolysis samples was 13.6% and 15.6%. Total error >15% TEa in the examination of insignificant hemolysis and mild hemolysis hemolysis samples was 27.2% and 31.2%. Conclusion: all the results of data analysis are outside the normal range and have a false decrease due to the addition of various levels of hemolysate, so the variation of insignificant hemolysis and mild hemolysis samples cannot be accepted or used in creatinine examination parameters.